2015
DOI: 10.3389/fmed.2015.00016
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Role of Retinoids in Glomerular Disease

Abstract: The primary etiology of CKD is a direct consequence of initial dysfunction and injury of the glomerulus, the main filtration system. Podocytes are terminally differentiated epithelial cells in the glomerulus, whose major function is the maintenance of this renal filtration barrier. Podocyte injury is implicated in many glomerular diseases including focal segmental glomerular sclerosis and HIV-associated nephropathy. In many of these diseased conditions, the podocyte can either undergo dedifferentiation and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…In our HFD-DN study, we did not detect changes to renal transcript levels of RARα across all experimental groups, but we did measure significant reductions in RARβ2, RARγ, and CRBP1 renal mRNA levels in HFD-fed mice. The trends of these findings are in agreement with a study by Ratnam et al (Ratnam et al, 2011) which demonstrated that renal levels of RARβ, but not RARα, are reduced in the CKD HIV-associated nephropathy (HIVAN) (Ratnam et al, 2011), despite evidence that RARα and RARα agonists are relevant to both the pathogenesis and treatment of HIVAN (Ratnam et al, 2011;Dai et al, 2017) and other CKDs (Ratnam et al, 2011;Zhong et al, 2011;Mallipattu and He, 2015). Our data, coupled to the Ratnam et al (Ratnam et al, 2011) demonstrating that the anti-CKD and podocyte-preserving effect of highly selective RARα agonists correlates with an increase in podocyte expression of RARβ only (Zhong et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our HFD-DN study, we did not detect changes to renal transcript levels of RARα across all experimental groups, but we did measure significant reductions in RARβ2, RARγ, and CRBP1 renal mRNA levels in HFD-fed mice. The trends of these findings are in agreement with a study by Ratnam et al (Ratnam et al, 2011) which demonstrated that renal levels of RARβ, but not RARα, are reduced in the CKD HIV-associated nephropathy (HIVAN) (Ratnam et al, 2011), despite evidence that RARα and RARα agonists are relevant to both the pathogenesis and treatment of HIVAN (Ratnam et al, 2011;Dai et al, 2017) and other CKDs (Ratnam et al, 2011;Zhong et al, 2011;Mallipattu and He, 2015). Our data, coupled to the Ratnam et al (Ratnam et al, 2011) demonstrating that the anti-CKD and podocyte-preserving effect of highly selective RARα agonists correlates with an increase in podocyte expression of RARβ only (Zhong et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…In the larger context of retinoid-CKD research, our findings highlight for the first time a potential role for RARβ2 in CKD, while the vast of majority of retinoid-CKD research has focused on a role for RARα, and the renal protective properties of RARα agonists (Lehrke et al, 2002;Ratnam et al, 2011;Zhong et al, 2011;Mallipattu and He, 2015;Dai et al, 2017). In our HFD-DN study, we did not detect changes to renal transcript levels of RARα across all experimental groups, but we did measure significant reductions in RARβ2, RARγ, and CRBP1 renal mRNA levels in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, RA has also been shown to attenuate inflammation and apoptosis in models of podocyte injury 39 . In this current study we sought to address whether RA can improve renal function and ameliorate kidney injury in the context of NTS-GN and whether this would be mediated directly through the inhibition of podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Rowe 577 et al showed that glycolysis has been increased in PKD and showed the treatment option by 578 inhibition of glycolysis which decreased the proliferation in PKD (171). Podocytes dedifferentiation 579 leading to glomerular dysfunction and ending in chronic kidney disease (CKD) has been shown 580 already, interestingly retinoids were used as a treatment option to reduce the glomerular dysfunction 581 and it was used as a differentiation therapy in this condition (172). Ascorbic acid as a differentiation 582 therapy may work in renal dysfunctions.…”
Section: B) 526mentioning
confidence: 99%